The Effect of University Students Readiness in Online Science Learning toward Learning Motivation - Rizki Wahyuningsih; Ika Maryani; Pratiwi Pujiastuti (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the effect of student readiness in online class on learning motivation. The population in this study were all 4th semester students with a sample of 80 students who were taken purposively. This research was conducted at Ahmad Dahlan University (UAD) in Yogyakarta. The time of this research was carried out for four months, namely from March to June 2021. The method used in this study was quantitative with a survey research design. The results of this study explain that the UAD PGSD Department students are ready to participate in online science learning during this pandemic, but it still has an impact on their enthusiasm or motivation to learn so that improvements are still needed from all parties to create a better online learning atmosphere. Improvements that can be made are in the form of providing online training or workshops for lecturers and students, improving e-learning management, providing education and motivation from lecturers to students regarding the positive side of e-learning, as well as increasing lecturer innovation so that e-learning implemented is more attractive to students. In addition, in the implementation of online-based learning, it is necessary to pay attention to the principles of learning, both for content and other activities prepared for online learning must be able to represent learning in the classroom, so that it becomes a challenge for lecturers in preparing online learning.